Moderate moralism: the aesthetic virtue and defect in Bob Dylan’s ‘Masters of War’ and ‘Neighbourhood Bully’ - Alotaibi, Sumaya Monaif (Penerbit Universiti Kebangsaan Malaysia, 2017)
No one can argue against the fact that the first thing that will keep the reader wanting to complete reading or to reread a literary text is the aesthetic experience that the work affords. This can be noticed when the perceiver faces any successful work of art. There is a sense of amusement and excitement (an aesthetic experience). This experience is emergent, formed as a result of the artistic value of the work. One of the elements comprising the artistic value is the moral dimension. Poems, and indeed any art work may hold moral value which will affect the experience of receiving them. The concept of moral value and its relation to aesthetic value in some art forms has been discussed by many scholars. This paper discusses the merit of Noel Carrol’s theory, moderate moralism. It then displays the moral virtues and defects of lyrics from two Bob Dylan’s songs, Masters of War and Neighbourhood Bully on the real readers’ aesthetic experience by using insights from moderate moralism, to establish the relationships between moral defects and virtues and their aesthetic value.